2003
DOI: 10.1023/a:1026174026995
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Clinoptilolite is a zeolite mineral with high cation exchange capacity used in zeoponic substrates that have been proposed as a solid medium for growing plants or as a fertilizer material. The kinetics of nitrification has not been measured for NH4+ saturated zeoponic substrate. Experiments were conducted to evaluate the production of NO2- and NO3-, and nitrifier populations in zeoponic substrates. Small columns were filled with zeoponic substrate inoculated with a commercial inoculum or soil enrichment cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…+ . Zeolite added to the field can adsorb the NH 4 + present in fertilizer, which is gradually desorbed and taken up by plants to inhibit nitrification of NH 4 + to NO 3 − , which improves plant growth and grain yield [43]. This was confirmed in the present study, where the zeolite-amended topsoil (0-30 cm) had a higher NH 4 + content than unamended soil in both years (Figure 4).…”
Section: Effect Of Irrigation Phosphorus and Zeolite Application On supporting
confidence: 83%
“…+ . Zeolite added to the field can adsorb the NH 4 + present in fertilizer, which is gradually desorbed and taken up by plants to inhibit nitrification of NH 4 + to NO 3 − , which improves plant growth and grain yield [43]. This was confirmed in the present study, where the zeolite-amended topsoil (0-30 cm) had a higher NH 4 + content than unamended soil in both years (Figure 4).…”
Section: Effect Of Irrigation Phosphorus and Zeolite Application On supporting
confidence: 83%
“…Mulch may increase the amount of N lost by volatilization, especially when urea is applied on soil surface. The N-urea losses can be reduced using zeolites as additives in the fertilizers to control the retention and release of NH 4 + [2,22].…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%
“…Adoption of management techniques such as clinoptilolite zeolite utilization, which maximizes N use efficiency and water use efficiency, may decrease the excessive and unbalanced use of N fertilizers in agriculture. Unbalanced use of N fertilizers could cause environmental pollution [ 11 ]. Studies have shown that the use of clinoptilolite zeolite and N fertilizers improves N use efficiency [ 12 – 15 ].…”
Section: Introductionmentioning
confidence: 99%